2007
DOI: 10.1080/10510970601168624
|View full text |Cite
|
Sign up to set email alerts
|

Deception and Emotion: The Effects of Motivation, Relationship Type, and Sex on Expected Feelings of Guilt and Shame Following Acts of Deception in United States and Chinese Samples

Abstract: This study explored whether people expect to experience guilt and shame following acts of deception, and whether such expectations are mediated by the deceivers' motivation, culture, sex, and=or the type of relationship between the deceiver and deceived. Students from China and the United States imagined themselves in several deception scenarios and rated the degree to which they would expect to experience guilt and shame following the deception. The scenarios depicted messages told for different reasons (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
1
33
2
1
Order By: Relevance
“…One study reported that women perceived deception as less acceptable and reported more intense emotional reactions to discovered deception (Levine, McCornack, & Baldwin, 1992). In addition, Seiter and Bruschke (2007) reported no sex differences in expected feelings of guilt and shame following the communication of deception. Because relevant research is limited, the following research questions were developed: RQ3a: Will the honesty=accuracy of organizational members' self-disclosure to a peer involved in a workplace romance differ based on the sex of the peer?…”
Section: Sex Of the Peer Involved In A Workplace Romancementioning
confidence: 99%
“…One study reported that women perceived deception as less acceptable and reported more intense emotional reactions to discovered deception (Levine, McCornack, & Baldwin, 1992). In addition, Seiter and Bruschke (2007) reported no sex differences in expected feelings of guilt and shame following the communication of deception. Because relevant research is limited, the following research questions were developed: RQ3a: Will the honesty=accuracy of organizational members' self-disclosure to a peer involved in a workplace romance differ based on the sex of the peer?…”
Section: Sex Of the Peer Involved In A Workplace Romancementioning
confidence: 99%
“…Emotions are significant factors in both relational communication in general and deception in particular (McCornack & Levine, 1990b;Seiter & Bruschke, 2007), in that encoding deceptive messages typically involves emotional processes (Ekman, 1997;McCornack & Levine, 1990a). Despite this, emotions remain underresearched variables in deception and relational research (McCornack & Levine, 1990b;Seiter & Bruschke, 2007).…”
Section: Guilt and Shamementioning
confidence: 99%
“…Yet, examining emotions in conjunction with deception has been branded an underresearched area (Seiter & Bruschke, 2007). The goal of this study was to discover if relational qualities (commitment and satisfaction) and the type of deceptive message communicated (lie, evasion, overstatement, concealment, or collusion) related to feelings of guilt and shame following deception.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Interestingly, Allingham and Sandmo (1972) explicitly mention that tax evasion may be limited if the individuals fear losing their reputation, but do not include this consideration in their model. In psychology, see Seiter and Bruschke (2007) on the role of guilt and shame in deception. 5 While pillories have been used in many cultures, the Web provides, nowadays, many examples of such policies.…”
Section: Introductionmentioning
confidence: 99%